2022
DOI: 10.21608/jesp.2022.257332
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Toxoplasmosis: An Overview on Transmission, Diagnosis and Treatment With Reference to Egypt

Abstract: Congenital toxoplasmosis is a zoonotic protozoan infection caused by the intracellular coccidian (phylum Apicomplexa) Toxoplasma gondii (T. gondii), which has a worldwide distribution. All warmis affected. The organism is transmitted transplacentally; following initial maternal infection, vertical transmission occurs from an infected pregnant mother to her fetus, mostly in the third trimester of pregnancy. The severity of fetal infection is determined by the pregnancy stage and whether the infected mother had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Review and Discussion Toxoplasmosis is found worldwide, and is estimated to have infected up to one-third of the global population (de Bles et al, 2021). It is a highly prevalent zoonosis where the definitive host of T. gondii is cat, which harbors the sexual parasitic cycle in the feline intestine and spreads infectious oocysts via feces, while the asexual reproduction of the parasite takes place in a broad spectrum of intermediate hosts, including humans who represent dead-end hosts of T. gondii (Imam et al, 2022). Human infection is often via the ingestion of sporulated oocysts detected on vegetables or in water and soil and eating raw or uncooked meat of infected animals.…”
Section: Introductionmentioning
confidence: 99%
“…Review and Discussion Toxoplasmosis is found worldwide, and is estimated to have infected up to one-third of the global population (de Bles et al, 2021). It is a highly prevalent zoonosis where the definitive host of T. gondii is cat, which harbors the sexual parasitic cycle in the feline intestine and spreads infectious oocysts via feces, while the asexual reproduction of the parasite takes place in a broad spectrum of intermediate hosts, including humans who represent dead-end hosts of T. gondii (Imam et al, 2022). Human infection is often via the ingestion of sporulated oocysts detected on vegetables or in water and soil and eating raw or uncooked meat of infected animals.…”
Section: Introductionmentioning
confidence: 99%